Extraction of phenolic composts and antioxidant activity of abacate shell (Persea Americana Mill) through different solvents (Research, Society and Development, 2022)
The objective was to evaluate the use of green solvents in the extraction of phenolic compounds from avocado peel. 7 solvents were tested: 1) ethanol (100%); 2) ethanol (50%) + distilled water (50%); 3) distilled water (100%); 4) lactic acid (100%); 5) lactic acid (50%) + distilled water (50%); 6) glycerin (100%); 7) glycerin (50%) + distilled water (50%). For the tests, approximately 5 grams of avocado peel and 100 mL of the tested solvent were used. For the extraction of total phenolic compounds, water + glycerin (50%) had the highest extraction potential with 609.9 mg EAG/L, with a variation of approximately 45% in relation to the solvent with the lowest yield (333.9 mg EAG/L) obtained with 100% ethanol. For DPPH, ethanol (100%); lactic acid (100%) and lactic acid (50%) + water (50%); showed statistical difference (p